INDOOR DUST EXPOSURE, SOCIO-DEMOGRAPHIC DETERMINANTS, AND SELF-REPORTED RESPIRATORY HEALTH BURDEN AMONG URBAN RESIDENTS OF BENIN CITY, NIGERIA: A CROSS-SECTIONAL STUDY. - O. ASEMOTA; E.A. OPHORI; O.I. ENABULELE (African Journal of Health, Safety and Environment, 2026)
Household dust is an important indoor health risk factor in sub-Saharan African cities undergoing rapid urbanization; however, few studies have characterized exposure and respiratory health risks associated with household dust in such populations. This cross-sectional study examined associations among socio-demographic factors, household dust exposure, and respiratory health among residents of Benin City, Nigeria. Structured interviews were conducted with 60 adults purposively sampled from three Local Government Areas. Self-reported socio-demographic variables, occupational and domestic dust exposures, and respiratory health outcomes (allergy, asthma, and rhinitis) were collected. Data were analysed using descriptive statistics and chi-square tests (p < 0.05) in SPSS v21. Most participants (75%) lived in multi-occupant households. Household dust/fume exposure occurred in 60% of respondents, while workplace exposure occurred in 65%. Atopic disease burden was high: 75% had previously suffered allergies, 30% had been diagnosed with asthma, and 75% suffered chronic/recurrent rhinitis. A family history of asthma was reported by 90% of participants. Occupational class (manual work) and residence in mixed-use areas were significantly associated with high household dust exposure (p < 0.05). Asthma was significantly associated with family history and self-reported household dust exposure. Overall, household dust exposure was more frequently reported among manual workers and residents of multi-occupant homes and was significantly associated with self-reported respiratory conditions.